2009
DOI: 10.1109/tasc.2009.2017919
|View full text |Cite
|
Sign up to set email alerts
|

Test Results of LARP ${\rm Nb}_{3}{\rm Sn}$ Quadrupole Magnets Using a Shell-Based Support Structure (TQS)

Abstract: Amongst the magnet development program of a large-aperture Nb 3 Sn superconducting quadrupole for the Large Hadron Collider luminosity upgrade, six quadrupole magnets were built and tested using a shell based key and bladder technology (TQS). The 1 m long 90 mm aperture magnets are part of the US LHC Accelerator Research Program (LARP) aimed at demonstrating Nb 3 Sn technology by the year 2009, of a 3.6 m long magnet capable of achieving 200 T/m. In support of the LARP program the TQS magnets were tested at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 19 publications
(15 reference statements)
1
24
0
Order By: Relevance
“…The results obtained by testing sample 3 shows clearly that a magnet based on this conductor and designed to reach its critical current at 4.2 K when the peak field in the coil is 12 T might reach its critical current at 4.2 K but it might be limited by the self-field instability at 1.9 K where the quench current might be even lower than that one at 4.2 K. Recent LARP magnet tests showed exactly this behavior [18].…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…The results obtained by testing sample 3 shows clearly that a magnet based on this conductor and designed to reach its critical current at 4.2 K when the peak field in the coil is 12 T might reach its critical current at 4.2 K but it might be limited by the self-field instability at 1.9 K where the quench current might be even lower than that one at 4.2 K. Recent LARP magnet tests showed exactly this behavior [18].…”
Section: Resultsmentioning
confidence: 62%
“…1). This behavior could explain the performance of the latest LARP magnets based on the RRP conductor that, at 1.9 K, had equal or even lower quench currents with respect to the 4.4 K case [15], [16], [18]. Strand measurements also showed that: 1) covering the strand with a 1 mm thick layer of stycast reduced the quench current at 1.9 K of less than 10%; 2) the strand self-field stability can be improved by reducing the strand diameter or by reducing the critical current density.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The primary goal of TQM01 was to test the mirror design and compare the quench performance of TQ coils in the mirror and quadrupole models. FIGURE 10 shows the training (left) and ramp rate (right) curves at 4.5 K for mirror TQM01 and quadrupoles TQC02E [9] and TQS02a [16]. All the models used regular TQ coils made of RRP-54/61 Nb 3 Sn strand with the only difference that the poles in coil #19 tested in TQM01 were bronze whereas the coils used in TQC02E and TQS02a had Ti poles.…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…The cable width was set close to the width of the LHC main dipole cable that is considered for the Phase I magnets. Nonetheless, the strand diameter was fixed at 0.7 mm used in the LARP TQ magnets [5]- [6]. For comparison purposes, a design based on NbTi cable with the same dimensions was also analyzed.…”
Section: Magnetic Designmentioning
confidence: 99%